Health Status Convergence at the Local Level: Empirical Evidence from Austria - Martin Gächter; Engelbert Theurl (University of Innsbruck, Department of Public Finance, 2010)
Health is an important dimension of welfare comparisons across individuals, regions or states. In the following paper we focus on the question whether the health status between geographical subunits (local communities) converged/diverged in the time period 1969 - 2004 in Austria. We use age standardized mortality rates as indicators for the health status and analyze the convergence/divergence of overall mortality for (i) the whole population, (ii) females, (iii) males and (iv) the gender gap in overall mortality. Convergence/Divergence is studied by applying different concepts of cross-regional inequality (weighted standard deviation, coefficient of variation, Theil-Coefficient of inequality). Various econometric techniques (weighted OLS, Quantile Regression, Kendall's Rank Concordance) are used to test for absolute and conditional beta-convergence in mortality. We find mixed results for the applied inequality measures. Absolute and conditional beta-convergence are confirmed, both in weighted OLS as well as in Quantile Regression estimations, but we also find strong evidence for the existence of convergence clubs in mortality in Austria.
Keywords: I10; I12; I18; 330; mortality; convergence; gender; health status; life expectancy; Austria